Brain Tumor Detection and Segmentation Using Conditional Random Field - Reddy, Vulavabeti Raghunath; Anusha, Shaik; Reddy, K Ravindra (International Journal of Computer Sciences and Engineering, 2019)
Medical image processing is a highly challenging field. Medical imaging techniques are used to image the inner portions of the human body for medical diagnosis. MR images are widely used in the diagnosis of brain tumor. In this paper, we present an automated method to detect and segment the brain tumor regions. The proposed method consists of three main steps: initial segmentation, modeling of energy functions and optimize the energy function. To make our segmentation more reliable we use the information present in the T1 and FLAIR MRI images. We use Conditional random field (CRF) based framework to combined the information present in T1 and FLAIR in probabilistic domain. A main advantage of CRF based framework is we can model complex shapes easily and we incorporate the observations in energy function.